1999
DOI: 10.1093/molehr/5.11.1059
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 receptors are expressed by basement membrane anchored, alpha6 integrin+ cytotrophoblast cells in early human placenta

Abstract: Cytotrophoblast cells produce interleukin (IL)-10 and express IL-10 receptor mRNA in culture. Furthermore, IL-10 dramatically reduces the synthesis of matrix metalloproteinase (MMP)-9 and the invasivity of cytotrophoblast cells in vitro, suggesting that an autocrine regulatory role in vivo is also possible. To test this hypothesis we investigated the expression of IL-10 receptor protein by first trimester cytotrophoblasts both in vitro and in situ, using flow cytometry and immunohistochemistry. Flow cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…38 IL-10 mRNA expression was studied using RT-PCR to validate the use of BeWo cells as a pertinent model for studying the influence of villous cytotrophoblast-derived factors, such as IL-10, on the functional phenotype of pro-inflammatory Mws. As expected, 28,29 undifferentiated BeWo cells express basal levels of IL-10 mRNA. However, we found that the IL-10/GAPDH ratio substantially increased from 0.260.1 to 0.760.…”
Section: Villous Cytotrophoblast-derived Factors Repress Stat1 Activasupporting
confidence: 84%
See 4 more Smart Citations
“…38 IL-10 mRNA expression was studied using RT-PCR to validate the use of BeWo cells as a pertinent model for studying the influence of villous cytotrophoblast-derived factors, such as IL-10, on the functional phenotype of pro-inflammatory Mws. As expected, 28,29 undifferentiated BeWo cells express basal levels of IL-10 mRNA. However, we found that the IL-10/GAPDH ratio substantially increased from 0.260.1 to 0.760.…”
Section: Villous Cytotrophoblast-derived Factors Repress Stat1 Activasupporting
confidence: 84%
“…55 Several lines of evidence suggest that IL-10 is an important suppressor of active maternal immunity that may be involved in the process of acceptance of the fetal allograft. 19,20,28,29 IL-10 levels increase markedly in women during early pregnancy and remain elevated up to the third trimester immediately prior to the onset of labor. Of note, compared to syncytiotrophoblasts, extravillous cytotrophoblasts are intrinsically poor in IL-10 production, 28,29 indicating that the syncytium might indeed contribute locally to counteract the deleterious effects of pro-inflammatory cytokines during early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations